Organic–inorganic covalent–ionic network enabled all–in–one multifunctional coating for flexible displays - Xiong Lin; Chen–Yu Li; Lu–Xuan Liang; Qing–Yun Guo; Yongzheng Zhang; Si–Rui Fu; Qin Zhang; Feng Chen; Di Han; Qiang Fu (Nature Communications)
Abstract Touch displays are ubiquitous in modern technologies. However, current protective methods for emerging flexible displays against static, scratches, bending, and smudge rely on multilayer materials that impede progress towards flexible, lightweight, and multifunctional designs. Developing a single coating layer integrating all these functions remains challenging yet highly anticipated. Herein, we introduce an organic–inorganic covalent–ionic hybrid network that leverages the reorganizing interaction between siloxanes (i.e., trifluoropropyl–funtionalized polyhedral oligomeric silsesquioxane and cyclotrisiloxane) and fluoride ions. This nanoscale organic–inorganic covalent–ionic hybridized crosslinked network, combined with a low surface energy trifluoropropyl group, offers a monolithic layer coating with excellent optical, antistatic, anti–smudge properties, flexibility, scratch resistance, and recyclability. Compared with existing protective materials, this all–in–one coating demonstrates comprehensive multifunctionality and closed–loop recyclability, making it ideal for future flexible displays and contributing to ecological sustainability in consumer electronics.